FORMATION OF CREATIVE ABILITIES OF STUDENTS AT STUDY OF PEDAGOGICAL DISCIPLINES IN TECHNOLOGICAL FACULTIES (Pedagogy of Higher and Secondary Education, 2008)
In article opportunities of formation of creative abilities of students are shown during teaching pedagogical disciplines on technologists by the check faculty.